2016
DOI: 10.3390/en9100763
|View full text |Cite
|
Sign up to set email alerts
|

Energy Consumption and Saving Analysis for Laser Engineered Net Shaping of Metal Powders

Abstract: Abstract:With the increasing awareness of environmental protection and sustainable manufacturing, the environmental impact of laser additive manufacturing (LAM) technology has been attracting more and more attention. Aiming to quantitatively analyze the energy consumption and extract possible ways to save energy during the LAM process, this investigation studies the effects of input variables including laser power, scanning speed, and powder feed rate on the overall energy consumption during the laser depositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Table 1. According to the values in Table 1, the theoretical energy density ɛ associated with the processes could be calculated by [43,44] h v…”
Section: Experimental Set-up and Parametersmentioning
confidence: 99%
“…Table 1. According to the values in Table 1, the theoretical energy density ɛ associated with the processes could be calculated by [43,44] h v…”
Section: Experimental Set-up and Parametersmentioning
confidence: 99%
“…Except for the research on the energy consumption of AM processes, the benefits of AM over SM regarding the energy saving and environmental problems reduction also have been well-documented in previous literature [11][12][13]. It was reported that AM process could simplify or shorten the energy-intensive processes-such as casting, forging, rough machining, etc.-during the SM; therefore, it will generate less environmental impacts [14]. Comparing the energy demand for AM and SM in manufacturing polymer products, Kreiger et al indicated that AM could reduce the energy consumption by 41 to 64% due to the direct fabrication [15].…”
Section: Introductionmentioning
confidence: 99%
“…Ultra-short pulsed laser ablation has received significant attention recently due to their better control, high power density, low energy dissipation, smaller heat-affected area, minimal collateral material damage, lower ablation thresholds, and excellent mechanical properties [1,2]. Therefore, Ultra-short pulsed laser ablation is being used in a variety of applications such as nanoparticle manufacturing [3,4], micromachining [5][6][7], surface modification [8], laser ablation propulsion [9], laser-induced breakdown spectroscopy [10], laser welding [11], among many others. During the ultra-short pulsed laser ablation process, the interaction between the laser beam and the target material will result in the ablation of the target and consequently the formation of a crater on the target surface [12].…”
Section: Introductionmentioning
confidence: 99%